TULISAN ARAB: PEMBINA TAMADUN ISLAM DI NUSANTARA - Cho, Taeyoung (Balai Arkeologi Sumatera Selatan, 2018)
This paper describes the role of Arabic script on a view of establishing Islamic civilization in Indonesian archipelago. Arabic script, apart from a tool for writing, its characteristic is so intensive to symbolize Islamic civilization. The arrival of Islamic civilization into the archipelago has not only spread the religion, but also influenced the change of social system in which Arabic script wrote the various spheres of Islamic civilization and transferred them into the local communities. The appearance of variant graphemes into the Arabic- based local scripts (Jawi, Pégon, Sérang, and Buri Wolio) is a result from the modification of Arabic script to the local languages for transmitting the elements of Islamic civilization to the contexts of local communities. In other words, Arabic script shifted Indonesian archipelago from the age of Jahiliah to the age of Islamic civilization.